Native point defect energies, densities, and electrostatic repulsion across (Mg, Zn)O alloys. Issue 7 (8th June 2015) - Foster, G. M.; Perkins, J.; Myer, M.; Mehra, S.; Chauveau, J. M.; Hierro, A.; Redondo‐Cubero, A.; Windl, W.; Brillson, L. J.
<x xml:space="preserve">Abstract</x> With the rise of MgZnO alloys as UV optoelectronic components, deep level defects in these materials have assumed added importance due to their impact on free carrier recombination, heterojunction band offsets, and Schottky barriers. Yet their dependence on alloy content and lattice structure is relatively unexplored. We have used depth‐resolved cathodoluminescence spectroscopy and nanoscale surface photovoltage spectroscopy to measure the dependence of native point defect energies and densities on Mg content, band gap, and lattice structure in non‐polar, single‐phase MgxZn1−xO (0 ≤ x ≤ 0.56) alloys grown by molecular beam epitaxy (MBE) on r‐plane sapphire substrates. Based on this wide range of alloy compositions, we identified multiple deep level emissions due to zinc and oxygen vacancies whose densities exhibit a pronounced minimum at ∼45% Mg corresponding to similar a and c parameter minima at ∼52%. This minimum also corresponds to a pronounced change in Schottky barriers reported previously. The reduction in unit cell volume appears to inhibit defect formation due to electrostatic repulsion as reflected in DFT calculations that assess the roles of electric fields and strain on the native defect distribution. These results highlight the coupled electronic and structural changes that occur across this wide alloy series.